Competing for the future: reconfiguring operational resources and capabilities during the digital transformation process - Féres, Wandick Leão (2022)
This doctoral dissertation aims to understand how incumbent firms reconfigure their operational resources and capabilities through digital transformation (DT). We suggest integrating operations strategy (OS) and resource orchestration (RO) to analyze this process. We applied a multiple case study with six incumbent Brazilian firms currently going through or have completed the DT. Regarding the theoretical framework, we first discovered how incumbent firms develop operational capabilities (OCs) through the DT process and found a pattern in the OCs developed (e. g., customization and cooperation). This pattern of OCs developed is intermediate by the phases of the DT process (e. g., digitization, digitalization, or DT). Second, these firms use customization and cooperation to achieve superior operational performance (OP) outputs such as speed and flexibility. These findings show coherence and mediation regarding the DT phase, OCs and OP developed by the incumbent firms. From a practical point of view, we make some recommendations for incumbent firms’ managers aspiring to engage the DT. First, they should diagnose what the DT phase of their firms is. Second, what resources and OCs are necessary for this phase? These combined actions will guide them to develop their DT process with efficacy and efficiency, considering the idiosyncrasies of their markets.